Fishing and Shipwreck Heritage : Marine Archaeology's Greatest Threat? - Kingsley, Sean A. (Debates in Archaeology Ser, 2015)
Cover -- Half-title -- Title -- Copyright -- Dedication -- Contents -- List of illustrations -- Preface -- Acknowledgements -- 1. Wrecks and Time Capsules -- 2. Trawling the Data -- 3. Bulldozers of the Deep -- 4. Scales of Heritage Impacts -- 5. Management Myopia -- 6. Conclusion: Seeking Sustainability -- Notes -- Bibliography -- Index.